DISEMINASI AKAD DAN PRODUK BANK SYARIAH PADA MASYARAKAT GAMPONG KEUDE KECAMATAN PEUDAWA ACEH TIMUR - Suryani, Suryani (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The purpose of this community service program is to increase an integrated and integrated understanding with the community and community leaders of Â Gampong Keude, Peudawa District, East Aceh, regarding products and products in Islamic banking. Sharia banking product and product disemination activities in the midst of the community need to be given to the speakers to gain insight into the Gampong Keude community about sharia banks. The results of this activity are the community, and Gampong Keude community leaders have knowledge of Islamic banking contracts and products and have an interest in joining Islamic banking in and around the city of East Aceh.Â